Case report of bullous pemphigoid in a 65 year old woman - Otikeodibi, Bolaji; Amadi, Ekechi S.; Altraide, Dasetima D.; Abbey, Belema O.; Ugwa, Okezie (International Journal of Research in Medical Sciences, 2020)
The unique thing about this case is that it is the first reported case of bullous pemphigoid in the elderly that has been clinically diagnosed with histologic findings highly suggestive of this blistering disorder although an immunofluorescence could not be done due to unavailability in the centre. Patient was managed successfully and discharged home with improvement on subsequent hospital visits. This case report shows how diagnosis of an immunobullous disease was made and managed in a resource poor setting. A descriptive summary of 65-year old black Nigerian woman with bullous pemphigoid covering history, physical examination and management. The main diagnosis was bullous pemphigoid in a recently diagnosed type 2 diabetic. Patient was placed on corticosteroids as well as immunosuppressive agents and diabetes was managed with subcutaneous insulin and oral hypoglycemics with appropriate wound care. Patient showed remarkable improvement after management and was discharged home with subsequent follow up in the clinics. Bullous Pemphigoid (BP) can be diagnosed clinically with a high index of suspicion with the aid of skin biopsy and histology, and can be managed successfully even in a resource poor centre where immunofluorescence facilities are lacking.